DEVELOPMENT OF PRAGMATIC APPROACH TO THE DEVELOPMENT OF STUDY TASKS IN HISTORY AND THE SKILLS OF ASKING QUESTIONS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article describes the development of pragmatic educational tasks for history lessons, the development of skills in formulating targeted questions and tasks, the creation of educational tasks that form students who think independently, can work independently with information, compare information, and extract the necessary ideas from it, the development of skills in formulating useful educational tasks of pragmatic content that can identify the most important, necessary information and topics for the student in the subject of history.